1983
DOI: 10.1111/j.1600-0447.1983.tb06978.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppression test in a pluri‐diagnostic approach: its relationship to psychopathological and clinical variables

Abstract: Using a pluridiagnostic approach, the dexamethasone suppression test (DST) was studied in 67 depressed inpatients in its relationship to diverse clinical variables. The International Classification of Diseases (ICD), the Research Diagnostic Criteria (RDC), the Newcastle Index, the Hamilton Depression Rating scale (HAM-D), and the Bf-s self rating questionnaire were applied. Fifty-two per cent of endogenous depressed (ICD), 51% of major depressive (RDC) and 53% of endogenous depressed (Newcastle) patients demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

1985
1985
1997
1997

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…No common factors were found. Miller and Nelson (51) reviewed 11 other studies (34,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65) that examined the relationship of individual symptoms to DST results. The most common symptom correlates of the DST were psychomotor change (both retardation and agitation) and sleep disturbance, followed by weight loss and somatic anxiety.…”
Section: Discussionmentioning
confidence: 98%
“…No common factors were found. Miller and Nelson (51) reviewed 11 other studies (34,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65) that examined the relationship of individual symptoms to DST results. The most common symptom correlates of the DST were psychomotor change (both retardation and agitation) and sleep disturbance, followed by weight loss and somatic anxiety.…”
Section: Discussionmentioning
confidence: 98%
“…A proportion (35 to 60 per cent) of patients with major depression show a disturbed DST (1)(2)(3)(4)(8)(9)(10). Some authors have found that patients with major depression exhibit a disturbed MHPG excretion (11)(12).…”
mentioning
confidence: 97%
“…The percentage of patients failing to suppress their cortisol production has varied considerably (17,18). The DST does not appear to distinquish unipolar from bipolar depression but may be useful as a marker in unipolar depression with a genetic background (19), although other authors have failed to confirm this finding (20).…”
mentioning
confidence: 91%